2014
DOI: 10.1371/journal.pone.0093724
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candidate Reference Genes in Perennial Ryegrass for Quantitative RT-PCR under Various Abiotic Stress Conditions

Abstract: BackgroundQuantitative real-time reverse-transcriptase PCR (qRT-PCR) is an important technique for analyzing differences in gene expression due to its sensitivity, accuracy and specificity. However, the stability of the expression of reference genes is necessary to ensure accurate qRT-PCR assessment of expression in genes of interest. Perennial ryegrass (Lolium perenne L.) is important forage and turf grass species in temperate regions, but the expression stability of its reference genes under various stresses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 54 publications
(57 reference statements)
2
64
0
Order By: Relevance
“…To our knowledge, the current study is the first to identify stable reference genes in leaves and roots of creeping bentgrass under different abiotic stresses (salt, drought, heat, and cold) using the combination of GeNorm, NormFinder, BestKeeper, and RefFinder (Andersen et al 2004;Vandesompele et al 2002). The previous study indicated that different reference genes could be determined by three different softwares (GeNorm, NormFinder, and BestKeeper) based on different mathematical methods or parameters (Chen et al 2014;Huang et al 2014;Zhu et al 2012). Therefore, a comprehensive analysis method named RefFinder was used to achieve reliable results based on the data of different softwares.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To our knowledge, the current study is the first to identify stable reference genes in leaves and roots of creeping bentgrass under different abiotic stresses (salt, drought, heat, and cold) using the combination of GeNorm, NormFinder, BestKeeper, and RefFinder (Andersen et al 2004;Vandesompele et al 2002). The previous study indicated that different reference genes could be determined by three different softwares (GeNorm, NormFinder, and BestKeeper) based on different mathematical methods or parameters (Chen et al 2014;Huang et al 2014;Zhu et al 2012). Therefore, a comprehensive analysis method named RefFinder was used to achieve reliable results based on the data of different softwares.…”
Section: Discussionmentioning
confidence: 99%
“…The four traditional reference genes (ACT, TUB, GAPDH, and EF1a) exhibited stable expression in certain plant species but had varied expressions in other species (Gimeno et al 2014;Huang et al 2014;Zhu et al 2013). For example, GAPDH was identified as the most stable reference gene in heat-stressed buffalograss (Buchloe dactyloides) ) but exhibited unstable expression in Oryza sativa under different environmental conditions (Jain et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gene expressing this protein has been shown to be stably expressed during drought and salt stress, but not necessarily during oxidative or other types of stress. 25 …”
Section: Protein Synthesis and Destinationmentioning
confidence: 99%